Percutaneous versus surgical closure of paravalvular leaks in prosthetic valves: A cross‐sectional comparison of clinical outcomes - Mohammadsaleh Baghi; Erfan Kohansal; Mahsa Akbarian; Sara Adimi; Hooman Bakhshandeh; Ata Firoozi; Pegah Salehi; Kasra Mehdizadeh; Hamed Hesami; Mina Yousefi; Sajjad Erami; Yeganeh Dehghani; et al. (Health Science Reports)
Abstract Background and Aims Paravalvular leak (PVL) is a serious complication of prosthetic valve replacement. Both surgical and percutaneous closure techniques are used for PVL closure, but optimal strategies and comparative outcomes are uncertain. This study aimed to compare the efficacy and safety of percutaneous versus surgical PVL closure by analyzing changes in leak severity, functional status, echocardiographic parameters, and clinical outcomes. Methods A total of 72 patients were included in this retrospective cross‐sectional single‐center study comparing percutaneous (n = 25) and surgical (n = 47) PVL closure from 2015 to 2022. Demographics, medical history, echocardiograms, laboratory data, complications, and mortality data were extracted from the records. Changes in leak severity, NYHA class, echocardiographic parameters, and clinical outcomes were compared between the percutaneous and surgical groups. Results Both percutaneous and surgical PVL closure significantly reduced leak severity and improved NYHA class (both p < 0.01), with no difference between the quantity of changes in each group. The 30‐day mortality was 4% after percutaneous and 6.4% after surgical closure (p = 0.65). At 90 days, mortality was 24% percutaneous versus 17% surgical (p = 0.48). The length of stay in the hospital and post‐procedural decrease in hemoglobin were considerably lower in the percutaneous group. The rate of complication rates was similar between the groups. Echocardiographic changes were also comparable. Conclusion Percutaneous and surgical PVL closure had similar efficacy in reducing leaks and improving symptoms, with no significant difference in early outcomes. Both options should be considered viable for PVL repair after heart team evaluation.